The CTS Gambit: Stanching the Federalization of Corporate Law - Alan R. Palmiter (Washington University Law Quarterly, 1991)
This Article sets out a federalism perspective on CTS and explores the wisdom of the Court's federalism gambit, comparing the current incorporation- based antitakeover regime with the likely product of a federal response. Part I considers the regulatory, market, and political landscape of corporate law and state antitakeover statutes. It explores the facilitative nature of state corporate law and its unique federalism implications, of which the relevant federal and state players have been acutely aware. Part II summarizes the CTS preemption and dormant commerce clause analysis, highlighting the Court's analytical and doctrinal foibles. It criticizes the Court's refusal to inquire meaningfully into the Indiana statute's political genesis or its effects, which the Court downplays in its preemption analysis and virtually disregards under the dormant commerce clause. This part asserts that CTS constitutionalizes the internal affairs doctrine-the state choice of law rule that the manager-shareholder relationship is governed by the law of the chartering state-and considers the extent to which the Court reserves a federalism gatekeeping role. Part III considers and rejects a variety of suggested hypotheses that explain CTS's blindness and its curious doctrinal results. In addition to exploring how the Court sought to preserve incorporation-based private ordering of corporate governance, it discusses the Court's attempts to minimize the possibility of any federal response. Part IV summarizes the current state of corporate federalism, in particular the response following CTS by the relevant players. It reaches some conclusions about the legality of the current and evolving antitakeover regime, conclusions that readily flow from a federalism perspective of CTS. Part V evaluates the forces that constrain antitakeover statutes at the state level and considers the wisdom of CTS, comparing the corporate political economy at the federal and state levels. It concludes that far more forces than recognized constrain state antitakeover statutes-for example, the threat of federal intervention (always looming in the wings) and the rhetoric of populism. It then considers the political stalemate that broad-based representation at the federal level has produced and, in the face of congressional paralysis, the Court's role as a catalyst for ensuring a legitimate federalism.
Keywords: Interstate commerce clause (Constitutional law); Exclusive & amp; concurrent legislative powers; Stockholders& #x27; voting; Tender offers (Securities); CTS Corp. v. Dynamics Corp. of America; 107 S. Ct. 1637